Alternatif Tren Studi Qur'an di Indonesia - M. Endy Saputro (AL-TAHRIR, 2011)
One of forces striking Qur ’anic studies in Indonesia is Qur ’anic textuality, which only able to reproduce debates around the issues of reconstruction of ulumul Qur’an in contemporary era. Furthermore, this trend seems to exclude another important issue on Qur ’anic studies in Indonesia, i.e. Qur’an in society. This paper aims to explore some alternative trends on the issues of Qur’an in society, arguing that the research subject of Qur ’anic studies in Indonesia should be humans, not Qur’an itself. Through this exploration, hopefully, research methodology and object of research on Qur ’anic studies increase with wide range of data and take important role in the shift of Islamic Studies in the world.